Reflexives Markers in Oceanic Languages1. (April 2017) - Moyse‐Faurie, Claire
Abstract: The goal of this article is to present a typological survey of reflexive markers found in Oceanic languages, their distributional properties, their uses and the notions they derive from. The low degree of grammaticalization of most of these markers largely explains the fact that they have often been overlooked. In Oceanic languages, morphological markers used to encode reflexivity usually differ from the ones used to encode reciprocal and middle situations. They are seldom obligatory, and their sources are strikingly diverse, either reflecting a larger range of the well‐known sources for intensifiers also used to encode reflexivity (such as expressions for body parts), or deriving from notions ('singularity', 'veracity' or 'spontaneity') rarely leading to markers of binding and co‐reference. Reflexive markers derived from spatial notions ('return', 'downwards') are also common in Oceanic languages, but seldom used as intensifiers.